Evaluation of Granite Fertility Utilizing Porphyry Indicator Minerals (Zircon, Apatite, and Titanite) and Geochemical Data: A Case Study from an Emerging Metallogenic Province in the Taimyr Peninsula, Siberian High Arctic - Stepan V. Berzin; Dmitry L. Konopelko; Sergei V. Petrov; Vasiliy F. Proskurnin; Evgeny I. Berzon; Mikhail Yu. Kurapov; Tamara A. Golovina; Natalya Ya. Chernenko; Vasiliy S. Chervyakovskiy; Roman S. Palamarchuk; Elena M. Andreeva (Minerals, 2024)
The Taimyr Peninsula in the Russian High Arctic comprises a late Paleozoic-early Mesozoic collisional belt where several porphyry-type mineralization occurrences were identified during the last decade, making this area a potential exploration target for Cu-Mo deposits. In order to further evaluate the metallogenic potential of the poorly outcropped northeastern part of Taimyr, samples from seven granitoid intrusions were investigated in this study aimed to evaluate the granite fertility based on petrography, geochemistry, and composition of porphyry indicator minerals (zircon, apatite, and titanite). The studied intrusions represent small to moderate-sized bodies (40–800 km2) composed of biotite (±amphibole) quartz monzonites, granodiorites, granites, and biotite leucogranites that formed in the course of late Paleozoic-early Mesozoic tectono-magmatic events at the Siberian margins. The late Carboniferous Tessemsky massif represents suprasubduction granitoid series, while the Pekinskiy, Shirokinskiy, Dorozhinskiy, Kristifensenskiy, and Yuzhno-Lodochnikovskiy massifs are correlated with the early Triassic Siberian Traps LIP. The rocks of intrusions comprise a relatively uniform geochemically, predominantly magnesian, slightly peraluminous, calc-alkaline high-K amphibole-bearing I-type granitoid series with adakitic affinity, where Triassic plume-related granitoids inherit geochemical signatures of Carboniferous supra-subduction granitoids, and all rock types are marked by enrichment in LILE and negative Ta, Nb, and Ti anomalies. It is suggested that the adakitic geochemical characteristics of the Taimyr granites are a result of derivation from a relatively homogeneous mafic lower crustal source that formed at the stage of Carboniferous continental subduction and continued to produce granitic melts in the course of the early Mesozoic magmatic evolution. Whole rock geochemistry and composition of porphyry mineral indicators (zircon, apatite, and titanite) indicate that the Taimyr granites crystallized from oxidized ...